2015
DOI: 10.1016/j.plrev.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Lévy behaviour in organisms – searching for a mechanism

Abstract: Please cite this article in press as: Sims DW. Intrinsic Lévy behaviour in organisms -searching for a mechanism. Phys Life Rev (2015), http://dx.doi.org/10. 1016/j.plrev.2015.06.002 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 24 publications
(51 reference statements)
2
17
0
Order By: Relevance
“…Additionally, we extended our model to show that for foragers in the wild with noisy temporal perception, the exponent of the best fit power law is governed by the nonlinearity of time perception and the amount of competition faced from other foragers. Thus, we contribute to the ongoing discussion regarding the mechanistic origins of power law path lengths in foragers (47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58) by arguing that search patterns are unlikely to be purely random when cognitive modeling is advantageous and that approximate power law path lengths emerge due to the temporal discounting of farther away rewards. A deeper understanding of the neurobiological basis of spatial search (59)(60)(61)(62)(63) may further enrich this model and provide greater insight into the movements of wild animals and humans.…”
Section: [2]mentioning
confidence: 99%
“…Additionally, we extended our model to show that for foragers in the wild with noisy temporal perception, the exponent of the best fit power law is governed by the nonlinearity of time perception and the amount of competition faced from other foragers. Thus, we contribute to the ongoing discussion regarding the mechanistic origins of power law path lengths in foragers (47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58) by arguing that search patterns are unlikely to be purely random when cognitive modeling is advantageous and that approximate power law path lengths emerge due to the temporal discounting of farther away rewards. A deeper understanding of the neurobiological basis of spatial search (59)(60)(61)(62)(63) may further enrich this model and provide greater insight into the movements of wild animals and humans.…”
Section: [2]mentioning
confidence: 99%
“…Sims [9] notes that some behavioural transitions, for example, switching between intensive and extensive modes of searching in C. elegans, can be heritable traits modifiable by the environment. This point is made explicitly in my Review [10]. There I suggested that mussels Mytilus edulis and the Australian desert ant Melophorus bagoti are perhaps the only known examples of selection for Lévy walking.…”
mentioning
confidence: 94%
“…The former predicts that Lévy walks will be common amongst probabilistic foragers, a prediction that I find to be incorrect. The later predicts that the occurrence of Lévy flights is accidental and uncommon even amongst probabilistic foragers and not restricted to searching, just as appears to be the case [10]. Sims [9] notes that some behavioural transitions, for example, switching between intensive and extensive modes of searching in C. elegans, can be heritable traits modifiable by the environment.…”
mentioning
confidence: 97%
See 2 more Smart Citations